EFEKTIVITAS BUKU GURU IPA BERBASIS PEMBELAJARAN TERPADU TIPE CONNECTED DENGAN TEMA FLUIDA DARAH - Amrina, Pebrisa (Institut Daarul Qur'an Jakarta, Indonesia, 2021)
The purpose of this study was to see the effectiveness of the integrated character-based teaching teacher books associated with the theme of blood fluids on the knowledge and skills of teachers based on the assessment of the Natural Science MGMP in Padang City. This type of research is development research with a ploomp development model consisting of preliminary research, prototyping phase, and assessment phase. Effectiveness is carried out in the assessment phase. The research instrument used was an observation sheet in the form of a questionnaire on teacher perceptions of teacher books and changes in teacher knowledge and skills after using the developed teacher book. Data analysis used descriptive analysis with data effectiveness analysis techniques using a Likert scale. The results showed that the dissemination of teacher books in the MGMP of Padang city with nine indicators obtained the average value of teacher perceptions of 83.33 in the very effective category, and the knowledge and skills of teachers with an indicator of 8 obtained an average of 88.54 categories of very effective. For the results of research on changes in knowledge obtained a value of 83.33 in the effective category and for changes in skills obtained a value of 91.27 for the category of very effective. Based on the results of the study, it can be concluded that the teacher's book is very effective for teacher knowledge and skills and deserves to be used as a guide for teachers in supporting the learning process and can be used as a guide for using student books in the same title.